Public goods versus the farm price-cost squeeze: shaping the sustainability of the EU’s common agricultural policy - Czyżewski, Bazyli; Matuszczak, Anna; Miśkiewicz, Radosław (Technological and Economic Development of Economy, 2019)
There is a consensus that farmers are subject to farm price-cost squeeze (PCS) when commodity prices fall and costs of production rise long-term. Willard Cochrane was the first to examine this phenomenon, introducing the notion that farmers are on a market treadmill. PCS is still a principle economic problem in agriculture touching farms in all over the world. It results from flexible prices but also from monopsony structures where recipients of commodities seize the opportunity of suboptimal pricing. Many studies indicate increasing retail farm price spreads but this lacks empirical studies on the effects of different types of subsidies on PCS. This work attempted to model EU Common Agricultural Policy (CAP) impact on PCS using the Constant Elasticity of Substitution (CES) production function, specified as in most CGE models. However, the authors tested the assumption of flexible prices reacting to changes in productivity. This approach is novel, while supported with an input-output analysis used to precisely decompose price and volume (productivity) effects at the level of a FADN representative farm. The results help to shape CAP shedding light on the present treadmill mechanism and showing that provision of public goods may be a remedy for market imperfections, whereas decoupled payments have the opposite influence.